Doppler Flow Indices and Prediction of Embryo Transfer Success and Pregnancy Outcome in Uterus Transplant Recipients - Johannesson, Liza; Testa, Giuliano; Borries, Trevor M.; Wall, Anji; Ma, Tsung-wei; Eagle, Elizabeth A.; Jain, Akshaya; Taylor, Sherri D.; dePrisco, Gregory; Gregg, Anthony R. (American Journal of Perinatology, 2023)
Objective Doppler velocimetry of the uterine and umbilical arteries is used to predict preeclampsia and monitor fetal outcomes. There have been no reports of Doppler velocimetry indices in pregnancies conceived after uterus transplantation, which differ from traditional pregnancies because of different uterine vascular inflow and outflow and exposure to immunosuppressive agents. We sought to examine whether Doppler indices can be used to predict embryo transfer success after uterus transplantation and whether Doppler indices across pregnancy predict fetal growth restriction.Study Design This was a single-center cohort observational study of 14 uterus transplant recipients who underwent embryo transfer. Of these, 12 women successfully delivered 14 babies. Five Doppler investigations were performed within the cohort: (1) prepregnancy; (2) uterine artery assessment across pregnancy; (3) umbilical artery assessment across pregnancy; (4) successive pregnancies; and (5) fetal growth.Results Prepregnancy uterine artery Doppler indices did not correlate with successful implantation after embryo transfer. Uterine artery Doppler indices in uterus transplant recipients decreased across pregnancy as described in pregnancies without uterus transplantation. The umbilical artery systolic/diastolic velocity ratio was lower at all weeks of gestation after uterus transplantation compared with values described in pregnancies without uterus transplantation. In those women who delivered two successive babies after uterus transplant, umbilical artery Doppler indices were significantly lower during the second pregnancy. There was always forward flow throughout diastole in the umbilical arteries, and no babies experienced fetal growth restriction.Conclusion In our study, uterus transplantation was not associated with abnormal blood flow indices in either the uterine or umbilical arteries. Although Doppler indices were not predictive of embryo transfer success, they supported the expectation that pregnancies after uterus transplantation at our center result in normally grown babies.Key Points
Keywords: uterus transplantation; pregnancy; umbilical artery; uterine artery; Doppler; systolic/diastolic velocity; resistive index; pulsatile index